Organisational climate and human resources: exploring a new construct in a cross‐national context. (4th September 2015) - Dastmalchian, Ali; McNeil, Nicola; Blyton, Paul; Bacon, Nicolas; Blunsdon, Betsy; Kabasakal, Hayat; Varnali, Renin; Steinke, Claudia
<x xml:space="preserve">Abstract</x> This paper reports the findings of an exploratory study which identifies aspects of organisational climate that relate to human resource management. A novel data analysis technique was employed to analyse qualitative data from interviews with 50 human resource managers in Australia, Canada and Turkey. The results identify four organisational climate dimensions that focus on HR issues and work environments. Based on the suggestions of the competing values framework and also on the literature concerning studies of societal culture, we labelled these climate dimensions as: 1) collaboration; 2) competition; 3) control; and 4) family‐orientation. These dimensions are seen to offer a path for future research on organisational climate and human resource management, and how employee's perceptions of the HR policies, practices and procedures may influence the efficacy of the HR function. Implications for studying these phenomena across different societies are addressed.